2019
DOI: 10.1016/j.jadohealth.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and Clinical Outcomes Among Young Adolescents Living With HIV in Kenya

Abstract: Purpose: Informing adolescents of their own HIV infection is critical as the number of adolescents living with HIV increases. We assessed the association between HIV disclosure and retention in care and mortality among adolescents aged 10-14 years in Kenya's national program. Methods: We abstracted routinely collected patient-level data for adolescents enrolled into HIV care in 50 health facilities from November 1, 2004, through March 31, 2010. We defined disclosure as any documentation that the adolescent had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 34 publications
5
37
6
Order By: Relevance
“…However parental disclosure has rarely been investigated in Ghana. This is consistent with how rare the practice of parental own status disclosure is among many HIV positive parents [22] [23].…”
Section: Discussionsupporting
confidence: 80%
“…However parental disclosure has rarely been investigated in Ghana. This is consistent with how rare the practice of parental own status disclosure is among many HIV positive parents [22] [23].…”
Section: Discussionsupporting
confidence: 80%
“…During follow-up, the cumulative death rate reached 3%. While this seems high, it is lower than that reported in other studies conducted in ALHIV in sub-Saharan Africa, where it ranged from 4-6% [33,51]. Although these rates remain in the same order of magnitude, our lower rate could be explained by the shorter follow-up duration.…”
Section: Discussioncontrasting
confidence: 79%
“…Many studies have reported on how HIV disclosure improves ALHIV clinical, immunological and virological outcomes as well as retention in care [28,32,33,51,52]. In COHADO, we found that HIV disclosure tend to reduce the odds of having a favorable 24-month outcome, though this was not significant.…”
Section: Discussioncontrasting
confidence: 67%
“…During follow-up, the cumulative death rate reached 3%. While this seems high, it is lower than that reported in other studies conducted in ALHIV in sub-Saharan Africa, where it ranged from 4-6% [33,51]. Although these rates remain in the same order of magnitude, our relative lower rate could be explained by the shorter follow-up duration.…”
Section: Discussioncontrasting
confidence: 77%
“…Many studies have reported on how HIV-disclosure improves ALHIV clinical, immunological and virological outcomes as well as retention in care [28,32,33,51,52]. In COHADO, we found that HIV-disclosure during COHADO tend to reduce the odds of having a favorable 24-month outcome, though this was not signi cant.…”
Section: Discussioncontrasting
confidence: 61%